Spatial dynamics: a new "milk corridor" in Paraná state, Brazil - Bankuti, Ferenc Istvan; Caldas, Marcellus Marques; Bankuti, Sandra Mara Schiavi; Granco, Gabriel (Semina: Ciências Agrárias, 2017)
Brazil is the fourth largest milk producer in the world, and Paraná state is the third largest producer in the country. Milk production plays an important socioeconomic role in Paraná state, and since the 1990s, institutional and market changes have influenced Paraná's milk production. Given this context, this study searches to analyze the spatial dynamics of dairy activity in Paraná state. Specifically, it seeks to identify areas of greater expansion and contraction in dairy activities, and discuss possible structural and socioeconomic consequences in those regions. Data concerning productive and economic variables of the 399 municipalities in Paraná state were used to generate an indicator of dairy activity through Common Factor Analysis. Cluster analysis allowed the formation of groups, according to municipalities' importance in Paraná's dairy activity. We conclude that since the 1990s, there has been displacement of dairy activity from the northern regions and toward the south. Dairy activity has started to occupy areas otherwise considered "agriculturally empty" and socioeconomically vulnerable. Those areas, along with traditional production regions, comprise a new "milk corridor" in Paraná. This may generate a set of socioeconomic benefits in the region. Important structural changes may occur along the dairy chain, and both public and private policies should be set to assure dairy chain competitiveness in Paraná state.